Water Resources and Fisheries Production Dynamics for Development of the Fisheries in Sepahijala District of Tripura, India - Biswas, Pradyut; Lahiri, Biswajit; Singh, Soibam Khogen; Shil, Bikash; Chakraborty, Ramanuj; Kumar, S T Pavan (Indian Journal of Extension Education, 2025)
Aquaculture, fisheries, and water resources are important to a region’s socioeconomic growth. The study was conducted by using a descriptive research design in all seven blocks of three sub-divisions of the Sepahijala district of Tripurato assess the water resources and utilisation dynamics for fisheries and aquaculture production in the district from the perspective of the development of fisheries in the region. Information regarding the study was based on the cross-sectional and time-series data, collected from the Department of Fisheries, Government of Tripura from 2016-18. The study revealed that culturable water resources were highest in the Sonamura subdivision and lowest in the Jampuijala subdivision. A similar trend was observed in capture fisheries and fish seed production. The study also confirmed the positive and significant relationship between total fish and prawn production in cultural fisheries and culturable water resources; total fish seed production and water were utilised for fish seed production; and between total fish and prawn production from capture fisheries resources with capture fisheries water resources. The study suggested formulating a meticulous strategy by identifying potential stakeholders, assessing availability, conserving, and ensuring proper utilisation of the water resources for the development of the fishers in the district.
Keywords: Culture and capture fisheries; Water resource utilisation; Fisheries production; Fish seed production; Fisheries development.